Function Changes on Brendung Art Performance in Sarwodadi Community Pemalang Regency: Between Preservation and Development - Nirwanto, Bagus; Cahyono, Agus; Utomo, Udi (Catharsis, 2021)
The purpose of this study is to analyze the shift of function in the context of art preservation and development on Brendung art perfomance in Sarwodadi community, Pemalang Regency. The research method used qualitative data and the research used a case study design. This research used both primary and secondary data sources and the data collection techniques used observation, interview, and document studies. The data analysis technique used interactive data analysis. Brendung is an art in Sarwodadi community, Pemalang and it is part of a performance, which shows a Brendung doll dance under the influence of spirits. The form of its performances have some changes in terms of a form of preservation effort, but it does not abandon the tradition or typical parts of Brendung art. Some preservation efforts of Brendung Art are done in order to maintain the existence of Brendung art itself so that it can still exist and is accepted by the society. The changes in the art are there but they do not abandon the old tradition. The shift of Brendung art performance in Sarwodadi community is as the effort so that the art will survive and does not disappear by the development of the era. It changes but it does not abandon the old tradition or the typical parts of Brendung art. Some preservation efforts of Brendung Art are done in order to maintain the existence of Brendung art itself so that it can still exist and is accepted by the society. The changes in the art are there but they do not abandon the old tradition. Brendung art was initially an art performance that functioned as a means of ritual and related to society and their belief, however, as the time goes by, it changes into an entertainment platform and aesthetic presence for its community.